Analysis of Timbal Metal (Pb) in a Carboned Canned Drink using Atom Absorption Spectrofotometer: Analisis Logam Timbal (Pb) dalam Minuman Kaleng Berkarbonasi dengan Menggunakan Spektrofotometer Serapan Atom - Fransisca Sara Maranatha; Argoto Mahayana (Program Studi S1 Teknik Kimia, Fakultas Teknik, Universitas Setia Budi, 2020)
Carbonated beverage cans are drinks that are supplemented with carbon dioxide (CO2), giving rise to gas bubbles to give freshness and quench your thirst when taken and drunk in cans. Cans are made of sheets coated with Tin (Sn) connected by an electric device such as soldered using Metal Lead (Pb) material, so that drinks can be contaminated by Metal Lead (Pb). Determination of Lead Metal (Pb) content in 3 different canned carbonated beverage brands is carried out by evaporating carbon dioxide (CO2) for 24 hours. Then the sample was acidified with concentrated HNO3 to pH <2 and filtered with Whatman filter paper No. 42, the resulting filtrate was analyzed with Atomic Absorption Spectrophotometer at a wavelength of 283.3 nm. Based on the results of the study, it was found that Lead Metal (Pb) levels in 3 Different brands of carbonated beverages are sample A 0.004 mg / L; B 0.002 mg / L; C 0.003 mg / L with a maximum limit of Lead Metal (Pb) content is 0.005 mg / L according to SNI 3708-2015 about Soda Water. Abstrak Minuman berkarbonasi kemasan kaleng merupakan minuman yang ditambah dengan karbondioksida (CO2) sehingga menimbulkan gelembung – gelembung gas untuk memberi kesegaran dan pelepas dahaga saat diminum yang dikemas dalam kemasan kaleng. Kaleng terbuat dari lembaran yang disalut dengan Timah (Sn) yang disambung dengan alat listrik seperti disolder yang menggunakan bahan Logam Timbal (Pb), sehingga minuman dapat terkontaminasi oleh Logam Timbal (Pb). Penentuan kadar Logam Timbal (Pb) dalam 3 merk minuman berkarbonasi kemasan kaleng yang berbeda dilakukan dengan menguapkan karbondioksida (CO2) selama 24 jam. Kemudian sampel diasamkan dengan HNO3 pekat sampai pH < 2 dan disaring dengan kertas saring Whatman no.42, filtrat yang dihasilkan dianalisis dengan Spektrofotometer Serapan Atom pada panjang gelombang 283,3 nm.Berdasarkan hasil penelitian, diketahui bahwa kadar Logam Timbal (Pb) dalam 3 merk minuman berkarbonasi yang berbeda adalah sampel A 0,004 mg/L; B 0,002 mg/L; C 0,003 mg/L dengan batas maksimum kadar Logam Timbal (Pb) adalah 0,005 mg/L sesuai SNI 3708- 2015 tentang Air Soda.